1957
DOI: 10.1021/j150557a004
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Chemistry of Organic Compounds. I. n-Alkane Liquids

Abstract: A series of -alkane liquids, pentane to hexadecane, have been irradiated with 800 kvp. electrons. The hydrogen yield, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1959
1959
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…G(H 2 ) values in the  and electron beam irradiated liquid n-alkanes are in the range of 430-545 nmolJ -1 [7,12,13]. In general, these values are lower for branched alkanes.…”
Section: Organic Phasementioning
confidence: 99%
See 1 more Smart Citation
“…G(H 2 ) values in the  and electron beam irradiated liquid n-alkanes are in the range of 430-545 nmolJ -1 [7,12,13]. In general, these values are lower for branched alkanes.…”
Section: Organic Phasementioning
confidence: 99%
“…In general, these values are lower for branched alkanes. For instance, G(H 2 ) is equal to 210 nmolJ -1 for 2,2-dimethylbutane [7] comparing with 520 nmolJ -1 for n-hexane [12]. Unsaturated alkanes reveal also lower G(H 2 ) values: for 1-hexene, G(H 2 ) is equal to 83 nmolJ -1 [14].…”
Section: Organic Phasementioning
confidence: 99%
“…This would favor neopentane formation over isopentane formation if the reaction occurred principally by a radical mechanism such as C^H 9 + CH 3 = 0^H 12 (37) or %H 9 + C U H 10 -C 5 H 12 + C 3 H 7 .…”
Section: P Cg Radiation Productsmentioning
confidence: 99%
“…Mass spectra observations (39) showed that the tertiary hydrogen of isobutane was removed 55 times more rapidly than, the primary hydrogen. This would favor neopentane formation over isopentane formation if the reaction occurred principally by a radical mechanism such as C^H 9 + CH 3 = 0^H 12 (37) or %H 9 + C U H 10 -C 5 H 12 + C 3 H 7 .…”
Section: P Cg Radiation Productsmentioning
confidence: 99%
“…These straight chain hydrocarbons had GfEg) values between lj.,2 and 5.2(3, 11,18,36,37). The yield of hydrogen in hydro carbons was essentially statistical in nature; as the branching The dependence of hydrogen and methane yield on temperature in the hydrocarbon increased the amount of hydrogen was found to decrease.The value of G(Eg) = 3*92 obtained in this investigation at 20°C is in agreement with the general trend of decreasing hydrogen with increasing branching.…”
mentioning
confidence: 97%